Estimation of seabed settlement during initial installation of a box-type artificial reef considering different seabed soil compositions and incident angles. (15th December 2020) - Han, Sol; Jung, Somi; Na, Won-Bae
Abstract: Some artificial reefs (ARs) have experienced an initial settlement primarily owing to their collision to the seabed during an installation process, particularly by a free-fall. This study presents a numerical estimation of the seabed settlement of a box-type artificial reef during the initial installation. For the purpose, the following works were implemented. First, a cube-type AR was selected because of its typical free-fall installation procedure, its facilitate volume (67.4%) in Korean coastal waters, and accumulated statistics showing severe seabed settlement. Second, numerical flow analyses were carried out to estimate the terminal velocities and distances of the AR in water. In this stage, four different incident angles were considered to calculate drag coefficients of the AR. Finally, numerical collision analyses were conducted to investigate the settlement characteristics of the seabed soils. For the analyses, three seabed soils (saturated sand, saturated sand and gravel, and saturated sand and clay) were considered. From the collision analysis, it is the saturated sand and clay composition to invoke higher settlement and accordingly higher loss of the effective useable volume (up to 25.5% at 45°). Therefore, it is recommended to avoid the seabed of any clay composition when we install artificial reefs during the free-fall installation. Highlights: Initial seabed settlement a box-type artificial reef was considered. Material models were used for saturated sand and its extensions to clay and gravel. We carried out collision analysis for three different seabed soil compositions. We estimated the initial settlements and losses of useable volumes of the AR. The procedure and estimation give useful insight for the AR management.